Why cognitive absorption is not enough: The role of knowledge absorption capacity and technological opportunity for individual learning - Ahmad Adeel; Samreen Batool; Daisy Mui Hung Kee; Zain-ul-Abdeen Madni (Asian Academy of Management Journal, 2023)
The purpose of this paper is to address the basic question why does high absorptive training programmes are not always beneficial for individual level learning? Thus, we seek to understand when and how cognitive absorption is beneficial for individual learning. The proposed model was tested using data obtained in a field study (N = 371) and in an experiment (N = 119). For field study, data was obtained at two points in time from three data sources (co-workers, subordinates, supervisors) working at a private commercial bank operating in Pakistan. For laboratory experiment, data was collected from the business students of a private sector university in Pakistan. The obtained data for both studies were analysed for random coefficient models with Mplus. Based on the motivation-ability-opportunity theory of behaviour, we proposed a model. It was found that cognitive absorption and highest individual learning was contingent upon the individual level knowledge absorption capacity. It was further found that training programmes with high cognitive absorption are likely to produce high levels of individual learning when the participants also have both high level of knowledge absorption capacity and technological opportunity. With this research, we inform practitioners that in these learner-focused trainings, personal characteristics of the participants and technology play vital role in determining effectiveness for high level of individual learning. The research findings will help practitioners understand what they need to add in training programmes for high level individual learning experience. Doing so will bring best value in form of higher learning to the cost of trainings.